Culinary preferences of foreign tourists in India. (January 2014) - Updhyay, Yogesh; Sharma, Dhiraj
Realizing the growing importance of culinary tourism, the present study explores culinary preferences of foreign tourists through surveys conducted at various tourist spots in India. In order to identify latent factors beneath, data related to preferences were factor analyzed. The outcome of the analysis suggests that tourists' preferences converge into five factors, namely, taste and quality of food, food preparation, localization of food and dining etiquettes, tradition and nutrition of food, and food aroma and cleanliness. Furthermore, convergence in foreign tourists was also explored based on their responses. From the analysis, three segments emerged, namely, taste seekers, localization seekers and experience seekers. The study also discusses the implications of the outcome for marketers and researchers.